Effect of di?etary vitamin e supplementation on the blood parameters of Nile Tilapia (Oreochromis Niloticus) - Ispir, U.; Yonar, M.E.; Oz, O.B. (My University, 2011)
This study evaluated the influence of diets supplemented with 0, 80, 160, 240 mg kg -1 (E 0, E 80, E 160, E 240) of vitamin E on the physiological responses of Nile tilapia (Oreochromis niloticus) fed for 3 months. Weight were not affected by dietary vitamin E concentrations. An increase (p<0.05) on the red blood cells count and on the hemoglobin concentration was obtained on treatments with 80 and 160 mg vitamin E kg -1 relativeto control. Mean corpuscular volume presented a significant increase (p<0.05) on treatment with 240 mg vitamin E kg -1 when compared to control. Mean corpuscular hemoglobin concentration was significantly decreased (p<0.05) on treatment with 240 mg vitamin E kg -1. The vitamin E treatments, we noticed a significant increase (p<0.05) in the number of leucocytes relative to control. Our results suggest that 80 mg vitamin E kg -1 is probably the most suitable concentrations for Tilapia diets, although high vitamin E diets are necessary for quantitative leucocyte increases for tilapia.
Keywords: Blood parameters; Nile tilapia; Oreochromis niloticus; Vitamin E